Evaluation of Mismatch Repair Gene Polymorphisms and their Contribution to Colorectal Cancer and its Subsets - Mrkonjic, Miralem
Colorectal cancer (CRC) is a major source of morbidity and mortality in the Western world. Approximately 15% of all CRCs develop via the mutator pathway, which results from a deficiency of mismatch repair (MMR) system and leads to genome-wide microsatellite instability (MSI). MLH1 promoter hypermethylation accounts for the majority of MSI CRCs. Numerous single nucleotide polymorphisms have been identified in MMR genes, however their functional roles in affecting MMR system, and therefore susceptibility to MSI CRCs, are unknown. This study uses a multidisciplinary approach combining molecular genetics, epigenetics, and epidemiology to examine the contribution of MMR gene polymorphisms in CRC. Among a panel of MMR SNPs examined, the MLH1 (-93G>A) promoter polymorphism (rs1800734) was shown to be associated with increased risk of MSI CRCs in two Canadian populations, Ontario and Newfoundland. Functional studies of the MLH1-93G>A polymorphism indicate that it has weak effects on the core promoter activity, although it dramatically reduces activity of the shorter promoter constructs in a panel of cell lines. Furthermore, MLH1 gene shares a bi-directional promoter with EMP2AIP1 gene, and the MLH1-93G>A polymorphism increases the activity of the reverse, EPM2AIP1 promoter. Examination of alternative role of the MLH1-93G>A polymorphism in MSI-H CRCs led to evaluation of a 500-kilobase pair chromosome 3 region around the MLH1 gene and identification of two additional SNPs, rs749072 and rs13098279, which are in strong linkage disequilibrium with rs1800734. All three SNPs showed strong associations with MLH1 promoter methylation, loss of MLH1 protein expression, and MSI-H CRCs in three populations, Ontario, Newfoundland, and Seattle. Such findings potentially implicate genetic susceptibility to DNA methylation. Logistic regression models for MSI-H versus non-MSI-H CRCs demonstrate that models including MLH1 IHC status and MLH1 promoter methylation status fit the data most parsimoniously in all three populations combined, however, when rs1800734/rs749072/rs13098279 was added to this model, polymorphisms no longer remained significant indicating that the observed associations of these polymorphisms with the MSI-H CRCs occur through their effect on DNA methylation. This study identified a novel mechanism in which common missense alterations may contribute to complex disease. PhD